The In-Flight Social Calls of Insectivorous Bats: Species Specific Behaviors and Contexts of Social Call Production - Springall, Brian T.; Li, Han; Kalcounis-Rueppell, Matina C. (Frontiers in Ecology and Evolution, 2019)
Bats could be a useful study system for studying the evolution of social communication, as they exhibit a high diversity of social group size and complexity. However, the study of bat social calls has been limited, as they are nocturnal, volant animals that produce predominately ultrasonic vocalizations. Passive acoustic monitoring studies occasionally capture bat in-flight social calls. The information from surrounding echolocation calls can provide information on species identity, activity level, and foraging behavior. We used passive acoustic monitoring in Greensboro, North Carolina, to identify seven types of in-flight social calls from Eptesicus fuscus, Lasiurus borealis, Lasiurus cinereus, Nycticeius humeralis, Perimyotis subflavus, and Tadarida brasiliensis. Eptesicus fuscus, N. humeralis, and T. brasiliensis differed in total social call production, and the proportional use of call types. Shared called types exhibited species-specific signatures, indicating the potential for bats to discern signaler identity. Social call production was positively correlated with bat activity. Social calls were often temporally clustered into independent social calling bouts. The complex and upsweep bouts of E. fuscus were associated with foraging, and the likelihood of complex bouts was negatively correlated with heterospecific activity. The production of N. humeralis downsweep, downsweep-upsweep, and upsweep bouts varied by season and site, but not according to bat activity, foraging, or time of night. Species differed in which call types were most commonly emitted, and these calls are associated with different contexts, suggesting that bats exhibit species-specific differences in in-flight social behavior.